A inserção do/a assistente social na escola : limites e possibilidades - Assunção, Paula de Ávila (2016)
The present argumentative text presents the results of an investigation about the insertion of Social Service in the school, as a public policy and educational, aiming to understand the possibilities and the limitations present in this reality. Consider the school community, the outside community and families, as subjects of this story and hear them, dialogically, as proposed by Paulo Freire, it was a great challenge. In the current conjuncture there is understanding that the Social Service is constituted as a mediator of the political processes that form the human culture, in the encounter with the other professions of Education. The presence of the social assistant at school implies a coherent commitment with the professional ethical-political project, hegemonic Brazilian Social Service, gestating since the end of the 1970s that should establish the School Pedagogic Project, a dialogic relationship. The research was developed in the Municipal School "Campo Florido” (fictitious name) in the city of Rondonópolis / MT. Participated as research subjects, two teachers, one general assistant, the coordinator and the director (representatives of the school community).Three mothers of students (representatives of Families) one of the oldest residents of the neighborhood - also community leadership, and the district president (External Community representatives). The research develops according to the critical qualitative theoretical framework. The theoretical-methodological foundations are rooted in Paulo Freire (1996, 2002, 2008) and also in relation to the theoretical frameworks and critical analysis of the data are considered Garske (2006), Time (2006), Iamamoto (2008) Netto (1998), Abreu (2004), Santos (2013) and Silva (2012).The research in their results revealed that between challenges and possibilities of insertion of social assistant at school is the desire of all subjects involved: school community, outside community and family, to that this fact occurs. According to the interviews, the limits for that the presence becomes effective as a public policy are: unavailability of professional in the context of municipal employees, assistentialistic vision of the profession and little knowledge of the Foreign Community and family about Democratic Management. And the possibilities are: the need for educational activities directed to the social issues developed by a professional with specific training, the mediator profile social worker and the space that the profession has won in this area, in other locations.